Outcomes of endoscopic retrograde cholangiopancreatography: a series from a provincial New Zealand hospital. Issue 3 (6th September 2016) - Richards, Simon; Kyle, Stephen; White, Campbell; El‐Haddawi, Falah; Farrant, Glenn; Henderson, Nigel; Fancourt, Michael; Gilkison, William
Abstract : Background: Endoscopic retrograde cholangiopancreatography (ERCP) is an essential tool in the management of pancreaticobiliary pathology. It is technically demanding and has the potential to cause significant morbidity and mortality. Several trials have identified small centres and lower hospital volume as risk factors for lower success rates and higher complication rates. Taranaki Base Hospital (TBH) is a provincial hospital with a catchment of 100 000, providing its population with an on‐site ERCP service. Transporting patients to the nearest tertiary centre would incur significant costs to both the patient and district health board. Aims: To determine the outcomes of performing ERCP at TBH and compare these with published figures. To determine if it is a safe and effective option for patients in this region. Methods: An ambi‐directional study of all ERCP procedures at TBH between January 2011 and December 2015 was conducted. Patient demographics, procedure indication and procedural details were captured via ProVation ® MD and endoscopist's notes. Complications were identified through patient's notes and recorded if occurring within 30 days of the procedure. All complications were graded mild, moderate or severe based on a grading system described by Cotton et al . Results: A total of 445 procedures were performed. Bile duct cannulation rate was 92.3% and therapeutic success rate was 89.9%. Complications occurred in 8.99% of patients and ERCP‐specific mortality was 0.22%. Haemorrhage occurred in 1.35% of patients, pancreatitis in 5.2% and perforation in 0.45%. Success and complication rates are similar to other published studies. Conclusion: ERCP can be safely and successfully performed in a provincial centre.